(untitled) - Frei, Frances; Frances Frei; Anne Morriss (Boston, Mass.)
In Uncommon Service, Frances Frei and Anne Morriss show how, in a volatile economy where the old rules of strategic advantage no longer hold true, service must become a competitive weapon, not a damage-control function. That means weaving service tightly into every core decision your company makes
Keywords: Customer relations; Customer services; Service industries